Impulsive stimulated Raman scattering in tetragonal GdVO4 single crystal: many-phonon Stokes and cross-cascaded lasing. (8th July 2015) - Yoneda, H; Zhang, J; Tang, D Y; Kaminskii, A A
Abstract: For the first time we excited four-phonon impulsive stimulated Raman scattering (SRS) in tetragonal GdVO4 single crystal under near-IR femtosecond pumping. All of its recorded χ (3) -nonlinear Stokes cascaded and cross-cascaded fully coherent lasing emissions were identified at internal vibrations of the [VO4 ] 3− units of the studied vanadate. The obtained new fundamental knowledge could significantly enrich the functional potential of this crystal, which is a host crystal for trivalent lanthanide lasants and attractive gain media for Raman laser converters and self-SRS lasers.